Arsenic content of raw and cooked rice and vegetables grown in Matlab area of Chandpur district of Bangladesh - Mahal, Zinat; Zahid, Hasan M; Wahed, MA; Yusuf, Harun KM (Dhaka University Journal of Biological Sciences, 2011)
Key words: Arsenic; Raw and cooked rice; Vegetables DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8948 DUJBS 2010; 19(1): 91-94